Differentiated Instruction Practices and Academic Achievement in Reading and Mathematics among Grade 2 Pupils in Philippine Public Schools - Jean A. Canilang; Nhelbourne K. Mohammad; Dwi Sulisworo (The Indonesian Institute of Science and Technology Research, 2026)
This study examined the relationship between teachers' differentiated instruction practices and the academic achievement of Grade 2 pupils in Reading and Mathematics in public elementary schools in the Division of Zamboanga del Norte, Philippines. Using a descriptive-correlational design with 492 teachers and their corresponding classes, the study found that differentiated instruction practices were frequently implemented across all dimensions. Pupils demonstrated satisfactory achievement in both Reading (M = 84.27) and Mathematics (M = 83.91). Correlation analysis revealed a significant moderate positive relationship between differentiated instruction and Reading achievement (r = 0.41, p < 0.001), and a significant weak positive relationship with Mathematics achievement (r = 0.38, p < 0.001). These findings suggest that responsive, differentiated teaching practices are meaningfully associated with foundational learning outcomes, particularly in literacy. The study recommends strengthening differentiated instruction through targeted professional development and instructional support.